Nilai –Nilai Kearifan Lokal Pulanga untuk Pengembangan Karakter - Djaelani Haluty (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
A great nation is a nation that has a strong character derived from the values emerged from the culture of its peoples. The values of local wisdoms are not barrier to progress in the global era; they will lead to a tremendous transformational force in improving the quality of human resources as a competitive advantage and comparative capital of a nation. Therefore, acknowledgment of the values of local wisdom is a strategic step in building the national character. ‘Pulanga’ is a philosophy that contains a comprehensive dimensional character. It is always meant an effort to increase the welfare of the people and encouraging attitudes and behavior of individuals who emphasize the harmony among human beings, between human and nature, and between human and God in making life and living.